2016
DOI: 10.1371/journal.pone.0146211
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Reverse Transcription PCR Assay for Detection of Senecavirus A in Swine Vesicular Diagnostic Specimens

Abstract: Senecavirus A (SV-A), formerly, Seneca Valley virus (SVV), has been detected in swine with vesicular lesions and is thought to be associated with swine idiopathic vesicular disease (SIVD), a vesicular disease syndrome that lacks a defined causative agent. The clinical presentation of SIVD resembles that of other more contagious and economically devastating vesicular diseases, such as foot-and-mouth disease (FMD), swine vesicular disease (SVD), and vesicular stomatitis (VS), that typically require immediate rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 16 publications
3
49
0
1
Order By: Relevance
“…These findings corroborate the results of recent reports that describe the association of SVA with vesicular disease and neonatal mortality in swine (7,9,10). Additionally, results here are consistent with studies that demonstrated the detection of SVA in vesicular fluid, lesion swabs, lesion scrapings, and oral swabs, indicating that these specimens are appropriate for SVA diagnosis (9,20). SVA nucleic acid has also been detected in serum and in various tissues from affected animals (lymph nodes, tonsil, spleen, and lung) (7,20).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings corroborate the results of recent reports that describe the association of SVA with vesicular disease and neonatal mortality in swine (7,9,10). Additionally, results here are consistent with studies that demonstrated the detection of SVA in vesicular fluid, lesion swabs, lesion scrapings, and oral swabs, indicating that these specimens are appropriate for SVA diagnosis (9,20). SVA nucleic acid has also been detected in serum and in various tissues from affected animals (lymph nodes, tonsil, spleen, and lung) (7,20).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, results here are consistent with studies that demonstrated the detection of SVA in vesicular fluid, lesion swabs, lesion scrapings, and oral swabs, indicating that these specimens are appropriate for SVA diagnosis (9,20). SVA nucleic acid has also been detected in serum and in various tissues from affected animals (lymph nodes, tonsil, spleen, and lung) (7,20). Notably, piglets that died during SVA outbreaks presented high viral loads in multiple tissues, including brain, liver, lung, heart, kidney, small intestine, and colon (10).…”
Section: Discussionsupporting
confidence: 88%
“…Compared with DNA virus, it's discovered that RNA virus, such as influenza virus, coronaviruses, exists a highly evolution rate [27e30]. Previous studies revealed that the prototype SVA isolate, namely SVV-001, was isolated in 2001 [31], and due to its selective tropism for human tumor cells, the virus was developed as an oncolytic agent [32].However, the basic viral pathogenesis was not detected accurately. In this study, the synonymous codon usage of the SVA was analyzed to better understand the SVA evolution, especially the interplay between the viruses and the immune response [33].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods such as conventional PCR, real‐time PCR, in situ hybridization technique‐RNAscope, nested‐PCR and massive parallel sequencing have been already available to be used in the detection of viral RNA of SVA (Bracht, O'Hearn, Fabian, Barrette, & Sayed, ; Dallagnol, Otonel, Leme, Alfieri, & Alfieri, ; Feronato et al., ; Fowler et al., ; Laguardia‐Nascimento et al., ; Pinheiro‐de‐Oliveira et al., ; Resende, Marthaler, & Vannucci, ; Vannucci et al., ). However, reverse transcriptase followed by droplet digital PCR (RT‐ddPCR) standardized in the present study offers a new methodology for detection and absolute quantification for Senecavirus A .…”
Section: Discussionmentioning
confidence: 99%